Method for improving fluctuation resistance of NiFe-LDH bimetallic oxyhydroxide catalytic material by electrolyte optimization based on first principle

Through first-principle calculation and optimization of acid ion adsorption configuration, the reconstitution of active centers and electrode inactivation caused by fluctuations in the surface pH of catalytic materials in renewable energy hydrogen production technology is solved, and the anti-fluctuation performance of catalytic materials is optimized and the electrode service life is extended.

CN119649932AInactive Publication Date: 2025-03-18SHENZHEN HINGEAR ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411724015.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the hydrogen production technology of renewable energy, fluctuations in the pH value of the electrolyte on the surface of the catalytic material lead to the reconstruction of the active center of the catalytic material and the inactivation of the catalytic electrode, shortening the service life and operation and maintenance cycle of the electrode.

Method used

Through first-principle relaxation calculation and acid ion adsorption configuration optimization, the adsorption configuration of suitable acid ions (such as borate, phosphate, carbonate) and NiFe-LDH bimetallic hydroxyoxide catalytic material surface are screened to optimize their fluctuation resistance.

Benefits of technology

The optimization of the acid ion adsorption configuration under fluctuation conditions is achieved, which improves the fluctuation resistance of the catalytic material, extends the service life of the electrode and maintains its excellent catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119649932A_ABST
    Figure CN119649932A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the fluctuation resistance of a NiFe-LDH bimetallic oxyhydroxide catalytic material by electrolyte optimization based on a first principle. The method comprises the following steps: performing relaxation calculation according to a first principle, cutting a low-Miller-index crystal face of a NiFe-LDH bimetallic oxyhydroxide crystal, and calculating system energy corresponding to a stable configuration of the crystal; establishing and constructing stable adsorption configurations of various acid radicals and the target on the basis of a first principle, performing relaxation calculation, and calculating corresponding system energy in an adsorption state; and calculating the total energy and the electronic structure of different acid radical ion adsorption states based on the original stable configuration energy and the adsorption state stable configuration energy obtained in the early stage. According to the method, a first principle is used for calculation, field experiments do not need to be carried out one by one for specific scenes, crystal track layout changes of various acid radical ions in the NiFe-LDH bimetallic oxyhydroxide catalytic surface adsorption process can be accurately estimated, and directional screening of specific acid radical adsorption on the anti-fluctuation performance of catalytic material optimization is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to a method for improving the anti-fluctuation performance of a NiFe-LDH bimetallic oxyhydroxide catalytic material by optimizing an electrolyte based on first principles. Background Art

[0002] In today's era, with the continuous growth of global energy demand and the increasing awareness of environmental protection, the development of renewable energy hydrogen production technology is particularly urgent and important. The over-exploitation and use of traditional energy such as coal, oil and natural gas has not only led to resource depletion, but also aggravated environmental pollution and climate change. Therefore, finding clean and sustainable energy alternatives has become a common issue faced by all mankind.

[0003] Renewable energy hydrogen production technology, especially the use of natural resources such as solar energy and wind energy to produce hydrogen through water electrolysis, provides a new way to solve the energy crisis and environmental pollution. This technology not only has a wide range of renewable raw materials, but also produces almost no greenhouse gas emissions during the production process, which meets the requirements of low-carbon environmental protection. Hydrogen produced by renewable energy can be used as an efficient energy carrier and is widely used in transportation, industry, electricity and other fields, helping to build a cleaner and more diversified energy system.

[0004] Renewable energy hydrogen production technology, as an important measure to cope with the dual challenges of energy crisis and environmental protection, is also the only way to drive the transformation and upgrading of energy structure and promote sustainable economic development. Its importance is self-evident. However, this technology faces a major problem in practical application: the inherent volatility of renewable energy causes the pH value of the electrolyte on the surface of the catalytic material to fluctuate dramatically. This change will not only trigger the reconstruction of the active center of the catalytic material, but also lead to the deactivation and shedding of the catalytic electrode, thereby greatly shortening the service life of the electrode and significantly reducing the operation and maintenance cycle. To meet this challenge, a potential solution is to add an appropriate amount of acid ions to the electrolyte to exert its pH buffering effect, thereby stabilizing the acid-base environment of the electrolyte. But at the same time, it is necessary to deeply explore the possible interactions between the acid ions and the surface of the catalytic material to ensure the effectiveness and reliability of the solution.

[0005] In order to solve the above problems, the present invention is proposed. Summary of the invention

[0006] The present invention aims to overcome the deficiencies of the prior art. The present invention provides a method for improving the anti-fluctuation performance of NiFe-LDH bimetallic oxyhydroxide catalytic materials by optimizing electrolyte based on first principles, and relates to the field of new material technology. The method includes: first-principles relaxation calculation, NiFe-LDH bimetallic oxyhydroxide crystal low Miller index crystal plane cutting, calculation of the system energy corresponding to the stable configuration of the crystal; based on the first-principles construction, constructing a variety of acid radicals (borates, phosphates, carbonates) and the target stable adsorption configuration and performing relaxation calculations, and calculating the corresponding system energy in the adsorption state; based on the original stable configuration energy and the adsorption state stable configuration energy obtained in the early stage, calculating the total energy and electronic structure of the adsorption state of different acid radical ions, and analyzing according to the electronic state density and electronic differential charge. Using first-principles calculation, there is no need to conduct field experiments one by one for specific scenarios, and the crystal orbital layout changes of various acid radical ions in the adsorption process of NiFe-LDH bimetallic oxyhydroxide catalytic surfaces can be accurately estimated, and the directional screening of specific acid radical adsorption for optimizing the anti-fluctuation performance of catalytic materials can be achieved.

[0007] The present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a method for improving the anti-fluctuation performance of a NiFe-LDH bimetallic oxyhydroxide catalytic material by optimizing an electrolyte based on first principles, comprising the following steps:

[0009] Step 1: Establish a supercell model of the NiFe-LDH bimetallic oxyhydroxide material with high activity for catalytic oxygen evolution, perform cell cutting on the low Miller index surface and establish a low index crystal surface, and construct a supercell structure model on the low index crystal surface according to the actual preparation situation;

[0010] Step 2: Calculate the electronic structure, differential charge distribution and crystal orbital layout of the relaxed configuration to clarify the initial structural data;

[0011] Step 3: Adsorb various acid radical ions on the relaxed configuration, screen and calculate the adsorption sites, and clarify the relaxed adsorption structure;

[0012] Step 4: Calculate the electronic structure, differential charge distribution and crystal orbital layout of the relaxed configuration of the adsorbed acid radical to obtain the adsorbed state structure data. Compare the various parameters of the initial structure data obtained in step 1 with the adsorbed state structure data to clarify the promoting effect of the acid radical ion adsorption, and then realize the use of electrolyte optimization to improve the anti-fluctuation performance of the NiFe-LDH bimetallic hydroxide catalytic material under fluctuating working conditions.

[0013] By screening the sites where acid ions are adsorbed on the unit cell cross-section, the effects and protective effects of adsorbed acid ions on the surface of catalytic materials are analyzed.

[0014] By analyzing the adsorption effects and bonding conditions of different acid ions through electronic localized functions, it is realized that the acid ions in the electrolyte can play a role in buffering the pH value under fluctuating conditions, ensuring that the catalytic material will not be affected by volatility and cause reconstruction of the surface active centers while still ensuring its excellent catalytic performance.

[0015] Preferably, step one is specifically:

[0016] The calculation method is to set the plane wave function basis vector cutoff energy to 700eV, set the self-consistent iterative process optimization electronic wave function algorithm to Fast algorithm, and combine DAV and RMM algorithms. The self-consistent iterative cycle convergence standard is set to 1E-4eV, the maximum number of self-consistent iterative cycles is set to 150, the ion step relaxation algorithm selects the conjugate gradient method, and the ion step relaxation control is set to full relaxation, which is suitable for most three-dimensional structure optimizations. The overall calculation accuracy control is set to Normal, the electronic orbital fraction occupation broadening method is set to Gaussian method, and the broadening width is set to the default 0.05eV. Since Fe and Ni are inherently magnetic, the electronic spin polarized atomic magnetic moments of Fe and Ni are set to 2 and 4. Van der Waals force correction is added on the basis of DFT calculation. The van der Waals force calculation method is DFT-D3 method. The Hubbard U (DFT+U) treatment method is used for transition metals Fe and Ni, and the p orbital U value of Fe is set to 5.3 and the p orbital U value of Ni is set to 6.45.

[0017] The lattice and atomic positions of the NiFe-LDH bimetallic oxyhydroxide unit cell were optimized. The lattice constants of the relaxed NiFe-LDH were a=12.00A, b=24.88A, c=36.79A, and the angles between the lattices were all 90°.

[0018] Preferably, step 2 is specifically:

[0019] The original NiFe-LDH relaxation structure wave function is read, and the electronic structure is calculated by increasing the number of Kohn-Sham orbitals, and the crystal orbital Hamiltonian layout function and charge distribution are calculated respectively.

[0020] Preferably, in step three, the plurality of acid ions include borate, phosphate and carbonate.

[0021] Preferably, step three is specifically:

[0022] The initial charge density ρ0 was set, and borate, phosphate, and carbonate were selected to operate on the low Miller index crystal plane of NiFe-LDH, and the relaxed adsorption structure was determined by the Kohn-sham equation, as shown below:

[0023]

[0024] First, based on the given initial charge density ρ0, the effective potential in the Kohn-Sham equation is determined. Subsequently, this equation is solved to obtain the single electron wave function, and the new charge density ρ is calculated using this wave function. Next, the difference between the newly calculated charge density ρ and the initial charge density ρ0 is compared. If the difference between the two is less than the preset convergence criterion, that is, the required accuracy requirement is met, the calculation process ends. On the contrary, if the convergence condition is not met, the new charge density ρ is mixed with the initial charge density ρ0 in a certain proportion to generate a new trial charge density, and the next iterative calculation is started. This iterative process will continue until the convergence criterion is reached, at which time the adsorption structure model reaches a stable state.

[0025] Preferably, step 4 is specifically as follows: reading the structural wave function data of NiFe-LDH adsorbed with acid ions (borate, phosphate, carbonate), calculating the electronic structure by increasing the Kohn-Sham orbital number, and calculating the crystal orbital Hamiltonian layout function and charge distribution, as described in the specification. Figure 2 As shown, the charge difference between the original structure and the adsorbed acid radical structure is calculated to obtain the adsorbed state differential charge, as shown in the instruction manual Figure 3 As shown. The crystal orbital Hamiltonian layout is obtained by calculating the wave function of the plane basis set. The specific formula is:

[0026] Φj(k,r)=cjμ(k)φμ(r)+cjν(k)φv(r)+…≈ψj(k,r).

[0027] According to the results of the crystal orbital Hamiltonian layout analysis, after the adsorption of different acid ions, the interaction between the surface Fe site and O is strengthened, and the original OER properties are changed. Moreover, the acid ions as strong proton acceptors can alleviate the pH changes around the electrode during the OER process, thereby improving the stability of the catalyst.

[0028] And according to the results of the crystal orbital Hamiltonian layout analysis, it is proved that after the adsorption of the acid radical ions, the valence of Fe increases and the valence state of the surface Ni decreases, which may be beneficial to the OER catalysis after activation. The increase in the valence state of Fe may be attributed to the strong interaction between the acid radicals, and the acid radical ions are in a higher negative charge state. At the same time, the high electron density around the acid radicals may affect the electronic state of the adjacent Ni in the lattice, resulting in a decrease in the Ni valence state. In summary, the acid radicals exist in the form of acid radical-Fe bonds. After activation in the electrolytic solution, the catalyst surface almost becomes an acid radical single bond (P, B, C)-O bond, which confirms the modification effect of the acid radical ions on the pre-designed electrocatalyst.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention utilizes first-principles calculations, without the need to conduct field experiments one by one for specific scenarios, to accurately estimate the changes in the crystal orbital layout of various acid ions during the adsorption process on the NiFe-LDH bimetallic hydroxide catalytic surface, thereby achieving targeted screening of specific acid adsorption for optimizing the anti-fluctuation performance of catalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the structural diagram of NiFe-LDH bimetallic hydroxide surface after relaxation after adsorption of various acid radicals.

[0032] Figure 2 Differential charge on the surface of NiFe-LDH bimetallic oxyhydroxide for the adsorption of various acid groups.

[0033] Figure 3 Comparison of the crystal orbital layout of various acid adsorption structures and the original structure of NiFe-LDH bimetallic hydroxide. DETAILED DESCRIPTION

[0034] The present invention is further described below by way of examples, which are not limited to the present examples. The experimental methods in the examples where specific conditions are not specified are generally carried out according to conventional conditions and conditions described in the manual, or according to the general equipment, materials, reagents, etc. used according to the conditions recommended by the manufacturer, which can be obtained from commercial channels unless otherwise specified. The technical scheme in the examples of the present invention will be described below in conjunction with the drawings in the examples of the present invention.

[0035] The present invention is based on the first principles and utilizes electrolyte optimization to improve the anti-fluctuation performance of NiFe-LDH bimetallic oxyhydroxide catalytic material. The specific steps of the method are as follows:

[0036] Step 1: Establish a supercell model of the NiFe-LDH bimetallic oxyhydroxide material with high activity for catalytic oxygen evolution, perform cell cutting on the low Miller index surface and establish a low index crystal surface, and construct a supercell structure model on the low index crystal surface according to the actual preparation situation;

[0037] Step 2: Calculate the electronic structure, differential charge distribution and crystal orbital layout of the relaxed configuration to clarify the initial structural data;

[0038] Step 3: Adsorb various acid ions (borate, phosphate, carbonate) on the relaxed configuration, screen and calculate the adsorption sites, and clarify the relaxed adsorption structure;

[0039] Step 4: Calculate the electronic structure, differential charge distribution and crystal orbital layout of the adsorbed acid radical relaxation configuration to obtain the adsorption state structure data. Compare the various parameters of the initial structure data obtained in step 1 with the adsorption state structure data obtained in step 4 to clarify the promoting effect of acid radical ion adsorption, and then realize the improvement of the anti-fluctuation performance of NiFe-LDH bimetallic hydroxide catalytic material by optimizing the electrolyte under fluctuating working conditions.

[0040] By screening the sites where acid ions are adsorbed on the unit cell cross-section, the effects and protective effects of adsorbed acid ions on the surface of catalytic materials are analyzed.

[0041] By analyzing the adsorption effects and bonding conditions of different acid ions through electronic localized functions, it is realized that the acid ions in the electrolyte can play a role in buffering the pH value under fluctuating conditions, ensuring that the catalytic material will not be affected by volatility and cause reconstruction of the surface active centers while still ensuring its excellent catalytic performance.

[0042] Step 1 is as follows:

[0043] The calculation method is to set the plane wave function basis vector cutoff energy to 700eV, set the self-consistent iterative process optimization electronic wave function algorithm to Fast algorithm, and combine DAV and RMM algorithms. The self-consistent iterative cycle convergence standard is set to 1E-4eV, the maximum number of self-consistent iterative cycles is set to 150, the ion step relaxation algorithm selects the conjugate gradient method, and the ion step relaxation control is set to full relaxation, which is suitable for most three-dimensional structure optimizations. The overall calculation accuracy control is set to Normal, the electronic orbital fraction occupation broadening method is set to Gaussian method, and the broadening width is set to the default 0.05eV. Since Fe and Ni are inherently magnetic, the electronic spin polarized atomic magnetic moments of Fe and Ni are set to 2 and 4. Van der Waals force correction is added on the basis of DFT calculation. The van der Waals force calculation method is DFT-D3 method. The Hubbard U (DFT+U) treatment method is used for transition metals Fe and Ni, and the p orbital U value of Fe is set to 5.3 and the p orbital U value of Ni is set to 6.45.

[0044] The lattice and atomic positions of the NiFe-LDH bimetallic oxyhydroxide unit cell were optimized. The lattice constants of the relaxed NiFe-LDH were a=12.00A, b=24.88A, c=36.79A, and the angles between the lattices were all 90°.

[0045] Step 2 is as follows:

[0046] The original NiFe-LDH relaxation structure wave function is read, and the electronic structure is calculated by increasing the number of Kohn-Sham orbitals, and the crystal orbital Hamiltonian layout function and charge distribution are calculated respectively.

[0047] Step three is as follows:

[0048] The initial charge density ρ0 was set, and borate, phosphate, and carbonate were selected to operate on the low Miller index crystal plane of NiFe-LDH, and the relaxed adsorption structure was determined by the Kohn-sham equation, as shown below:

[0049]

[0050] First, based on the given initial charge density ρ0, the effective potential in the Kohn-Sham equation is determined. Subsequently, this equation is solved to obtain the single electron wave function, and the new charge density ρ is calculated using this wave function. Next, the difference between the newly calculated charge density ρ and the initial charge density ρ0 is compared. If the difference between the two is less than the preset convergence criterion, that is, the required accuracy requirement is met, the calculation process ends. On the contrary, if the convergence condition is not met, the new charge density ρ is mixed with the initial charge density ρ0 in a certain proportion to generate a new trial charge density, and the next iterative calculation is started. This iterative process will continue until the convergence criterion is reached, at which time the adsorption structure model reaches a stable state.

[0051] Step 4 is as follows: Read the structural wave function data of NiFe-LDH adsorbed with borate, phosphate and carbonate, calculate the electronic structure by increasing the Kohn-Sham orbital number, and calculate the crystal orbital Hamiltonian layout function and charge distribution, as shown in the instruction manual. Figure 2 As shown, the charge difference between the original structure and the adsorbed acid radical structure is calculated to obtain the adsorbed state differential charge, as shown in the instruction manual Figure 3 As shown. The crystal orbital Hamiltonian layout is obtained by calculating the wave function of the plane basis set. The specific formula is:

[0052] Φj(k,r)=cjμ(k)φμ(r)+cjν(k)φv(r)+…≈ψj(k,r).

[0053] According to the results of the crystal orbital Hamiltonian layout analysis, after the adsorption of different acid ions, the interaction between the surface Fe site and O is strengthened, and the original OER properties are changed. Moreover, the acid ions as strong proton acceptors can alleviate the pH changes around the electrode during the OER process, thereby improving the stability of the catalyst.

[0054] And according to the results of the crystal orbital Hamiltonian layout analysis, it is proved that after the adsorption of the acid radical ions, the valence of Fe increases and the valence state of the surface Ni decreases, which may be beneficial to the OER catalysis after activation. The increase in the valence state of Fe may be attributed to the strong interaction between the acid radicals, and the acid radical ions are in a higher negative charge state. At the same time, the high electron density around the acid radicals may affect the electronic state of the adjacent Ni in the lattice, resulting in a decrease in the Ni valence state. In summary, the acid radicals exist in the form of acid radical-Fe bonds. After activation in the electrolytic solution, the catalyst surface almost becomes an acid radical single bond (P, B, C)-O bond, which confirms the modification effect of the acid radical ions on the pre-designed electrocatalyst.

[0055] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for improving the anti-fluctuation performance of NiFe-LDH bimetallic oxyhydroxide catalytic material by optimizing electrolyte based on first principles, characterized in that: The steps include: Step 1: Establish a supercell model of the NiFe-LDH bimetallic oxyhydroxide material with high activity for catalytic oxygen evolution, perform cell cutting on the low Miller index surface and establish a low index crystal surface, and construct a supercell structure model on the low index crystal surface; Step 2: Calculate the electronic structure, differential charge distribution and crystal orbital layout of the relaxed configuration to clarify the initial structural data; Step 3: Adsorb various acid radical ions on the relaxed configuration, screen and calculate the adsorption sites, and clarify the relaxed adsorption structure; Step 4: Calculate the electronic structure, differential charge distribution and crystal orbital layout of the relaxed configuration of the adsorbed acid radical to obtain the adsorbed state structure data. Compare the various parameters of the initial structure data obtained in step 1 with the adsorbed state structure data to clarify the promoting effect of the acid radical ion adsorption, and then realize the use of electrolyte optimization to improve the anti-fluctuation performance of the NiFe-LDH bimetallic hydroxide catalytic material under fluctuating working conditions.

2. According to claim 1, the method for improving the anti-fluctuation performance of NiFe-LDH bimetallic oxyhydroxide catalytic material by optimizing the electrolyte based on the first principles, characterized in that: In step 1, the calculation method is to set the plane wave function basis vector cutoff energy to 700 eV, set the self-consistent iterative process to optimize the electron wave function algorithm to the Fast algorithm, and combine the DAV and RMM algorithms.

3. According to claim 1, the method for improving the anti-fluctuation performance of NiFe-LDH bimetallic oxyhydroxide catalytic material by utilizing electrolyte optimization based on first principles is characterized in that: In step 2, the original NiFe-LDH relaxed structure wave function is read, and the electronic structure is calculated by increasing the number of Kohn-Sham orbitals, and the crystal orbital Hamiltonian layout function and charge distribution are calculated respectively.

4. According to claim 1, the method for improving the anti-fluctuation performance of NiFe-LDH bimetallic oxyhydroxide catalytic material by optimizing the electrolyte based on the first principles, characterized in that: In step three, the various acid ions include borate, phosphate and carbonate.

5. According to claim 1, the method for improving the anti-fluctuation performance of NiFe-LDH bimetallic oxyhydroxide catalytic material by utilizing electrolyte optimization based on first principles, characterized in that: In step 3, the initial charge density ρ0 is set, borate, phosphate, and carbonate are selected to operate on the NiFe-LDH low Miller index crystal plane, and the relaxed adsorption structure is determined by the Kohn-sham equation. The calculation process is based on the Kohn-sham equation:

6. The method for improving the anti-fluctuation performance of NiFe-LDH bimetallic oxyhydroxide catalytic material by utilizing electrolyte optimization based on first principles according to claim 1, characterized in that: In step 4, the structural wave function data of NiFe-LDH adsorbing acid ions are read, and the electronic structure is calculated by increasing the Kohn-Sham orbital number to calculate the crystal orbital Hamiltonian layout function and the charge distribution, respectively.

7. The method for improving the anti-fluctuation performance of NiFe-LDH bimetallic oxyhydroxide catalytic material by utilizing electrolyte optimization based on first principles according to claim 1, characterized in that: In step 1 and step 4, the crystal orbital layout calculation process is based on the plane wave basis set wave function: Φj(k,r)=cjμ(k)φμ(r)+cjν(k)φv(r)+…≈ψj(k,r).